Copyright situation in the Republic of Croatia - Mikelić, Nives; Miškić, Jelena (2003)
The subject of this paper is the specific situation of the present copyright law in the Republic of Croatia. In order to discuss ways how to synchronize with the copyright legislation in the EU, we compared the situation in our country with the copyright legislations in the Eastern European countries and also the current copyright law with the EU copyright directives. At this moment Croatian copyright law is under construction and it must be adopted in accordance with the EU copyright directive by the end of the year 2005. Because of new, emerging publications, new necessary demands have been imposed by individuals and institutions for the protection of intellectual property as well. The current situation in Croatia shows that there is no law considering copyright in the digital environment. In absence of appliable legislation, rights, which have been guaranteed to the authors and, which are valid for the analog media are momentarily also applied to the digital media. Hot copyright matter concerns prevailing and unifying demands between the legislators, authors, publishers, librarians and users in order to participate in the homogenization of the copyright in the EU.
Projekt MZOS
ENG